العلاقة بين الاحتراق النفسى والرضا الوظيفى لدى معلمات التعليم العام ومعلمات التربية الخاصة فى المملكة العربية السعودية : دارسة مقارنة - حسن، نجوى حسن على; الجلامدة، فوزية عبدالله (رابطة التربويين العرب, 2013)
هدفت الدراسة إلى التعرف على نوع العلاقة بين الاحتراق النفسي والرضا الوظيفي لدى معلمات التعليم العام، ومعلمات التربية الخاصة لمختلف مجال التخصص، بالإضافة إلى المقارنة بين مستويات أبعاد الاحتراق النفسي لدى معلمات التربية الخاصة بمختلف التخصصات. وقد تكونت الدراسة من (225) معلمة من معلمات التعليم العام، ومعلمات التربية الخاصة. واستخدمت الباحثتان في هذه الدراسة مقياس ماسلاش وجاكسون للاحتراق النفسي، ومقياس الرضا الوظيفي لستمبن ولوب. وأشارت نتائج الدراسة إلى وجود فروق دالة إحصائياً بين معلمات التعليم العام، ومعلمات التربية الخاصة على مقياس الاحتراق النفسي ولصالح معلمات؛ التعليم العام، كما وجدت فروق دالة إحصائياً بين معلمات التعليم العام، ومعلمات التربية الخاصة علي مقياس الرضا الوظيفي ولصالح معلمات التعليم العام، كما أسفرت نتائج الدراسة إلى وجود فروق دالة إحصائياً بين معلمات التربية الخاصة باختلاف التخصص على مقياس الاحتراق النفسي، بينما لا توجد فروق دالة إحصائياً بين معلمات التربية الخاصة بمختلف التخصصات على أبعاد مقياس الرضا الوظيفي. كما أشارت النتائج إلى وجود علاقة ارتباطيه عكسية بين الاحتراق النفسي والرضا الوظيفي، أي كلما كان لدى المعلمات احتراق نفسي مرتفع، كلما قل الرضا الوظيفي لديهن، وكلما قل الاحتراق النفسي، كلما ارتفع معدل الرضا الوظيفي. وقد ناقشت الباحثتان في نهاية البحث مجموعة من التوصيات المتعلقة بمعلمات التعليم العام ومعلمات التربية الخاصة المتعرضات للاحتراق النفسي. The aim of the study is to identify the type of relationship between burnout and job satisfaction among the parameters of public education, and special education teachers to a different area of specialization. Also it aims to hold a comparison between the levels of burnout dimensions of special education teachers in various disciplines .The study consisted of (225) parameter of public school, and special education teachers. In the current study, the researchers used Mas lash measure and psychological Jackson combustible, and a measure of job satisfaction to Stmben and Loeb. The results indicated that there were statistically significant differences between the parameters of public education, and teachers of special education on a scale burnout and for parameters of public education, also found statistically significant differences between the parameters of public education, and teachers of special education on a scale of job satisfaction and benefit parameters of public education. The study also yielded results that there are significant differences between special education teachers in different specialization on a scale burnout, while there are no statistically significant differences between the parameters of special education in various disciplines on the dimensions of a measure of job satisfaction. The results also indicate that there is an inverse correlation between burnout and job satisfaction, i.e. whenever the high combustion parameters myself the less job satisfaction have, and the less burnout, the higher the rate of job satisfaction. The researchers discussed at the end of the research group of recommendations relating to public education parameters and special education teachers subjected to psychological combustion.
784776
Keywords: الصحة النفسية -- معلمات التعليم العام -- معلمات التربية الخاصة -- تعليم ذوى الاحتياجات الخاصة -- الرضا الوظيفى -- الاضطرابات النفسية -- الضغوط النفسية -- الصحة النفسية -- المعوقون